Global fund financing to the 34 malaria-eliminating countries under the new funding model 2014–2017: an analysis of national allocations and regional grants. (December 2016) - Zelman, Brittany; Melgar, Melissa; Larson, Erika; Phillips, Allison; Shretta, Rima
Abstract Background The Global Fund to Fight AIDS, Tuberculosis, and Malaria (GFATM) has been the largest financial supporter of malaria since 2002. In 2011, the GFATM transitioned to a new funding model (NFM), which prioritizes grants to high burden, lower income countries. This shift raises concerns that some low endemic countries, dependent on GFATM financing to achieve their malaria elimination goals, would receive less funding under the NFM. This study aims to understand the projected increase or decrease in national and regional funding from the GFATM's NFM to the 34 malaria-eliminating countries. Methods Average annual disbursements under the old funding model were compared to average annual national allocations for all eligible 34 malaria-eliminating countries for the period of 2014–2017. Regional grant funding to countries that are due to receive additional support was then included in the comparison and analysed. Estimated funding ranges for the countries under the NFM were calculated using the proposed national allocation plus the possible adjustments and additional funding. Finally, the minimum and maximum funding estimates were compared to average annual disbursements under the old funding model. Results A cumulative 31 % decrease in national financing from the GFATM is expected for the countries included in this analysis. Regional grants augment funding for almost half of the eliminating countries, and increase the cumulative percent change in GTFAM funding to 32 %, though proposed activities may not be funded directly through national malaria programmes. However, if countries receive the maximum possible funding, 46 % of the countries included in this analysis would receive less than they received under the previous funding model. Conclusions Many malaria-eliminating countries have projected national declines in funding from the GFATM under the NFM. While regional grants enhance funding for eliminating countries, they may not be able to fill country-level funding gaps for local commodities and implementation. If the GFATM is able to nuance its allocation methodology to mitigate drastic funding declines for malaria investments in low transmission countries, the GFATM can ensure previous investments are not lost. By aligning with WHO's Global Technical Strategy for Malaria and investing in both high- and low-endemic countries, the Global Fund can tip the scale on a global health threat and contribute toward the goal of eventual malaria eradication.